The teaching-learning process of Financial Mathematics from the Historical-Cultural approach - Villamar Gavilanes, Ana (2022)
This paper emerged as a synthesis of the first chapter of the doctoral thesis called "Didactic strategy for the Financial Mathematics subject in the Business Administration Career of the State University of Milagro in the Republic of Ecuador". The objective of this paper is to systematize the theoretical-methodological references that support the teaching-learning process of the Financial Mathematics subject from the Historical-Cultural approach. For this, a documentary research was carried out that supports that any process of teaching-learning of Financial Mathematics subject must be based on the development of thought, reasoning and social awareness, cognitive skills that facilitate problem solving and decision-making in environments of uncertainty